Linking farmers and schools to improve diets and nutrition in Busia County, Kenya - Borelli, Teresa; Hunter, Danny; Wasike, Victor W.; Wasilwa, Lusike; Manjella, Aurillia (Food and Agriculture Organization of the United Nations, 2021)
Chapter provides an overview to the school food procurement pilot study in Busia County, Kenya aimed at providing African leafy vegetables for diversification of school meals.